Optimalisasi Kompetensi SDM dan Strategi Marketing Kreatif guna Mewujudkan Financial Stability pada UKM HF Gold Serang Banten - Sasmita Sari Ardaninggar; Vivi Iswanti Nursyirwan (Jurnal PKM Manajemen Bisnis, 2026)
Small and Medium Enterprises (SMEs) play a crucial role in supporting Indonesia’s economic growth. However, most SMEs still operate on a micro scale and face various challenges, including limited human resource competencies, uneven digital adoption, restricted market reach, and inadequate financial management practices. These challenges were also experienced by HF Gold Serang, a community-based precious metal trading business operating under Islamic principles, which affected its financial stability. To address these issues, a Community Service Program (PKM) was conducted by a team of three lecturers and students from the Undergraduate Accounting Program of Universitas Pamulang. The activity was held online via Zoom on May 16, 2026, involving 15 participants from the HF Gold Serang community. The program employed a participatory, practical, and sustainable approach based on the concepts of capacity building and learning by doing. The implementation included presentations, discussions, case studies, simulations, and mentoring activities. The training focused on three main aspects: optimizing six essential human resource competencies, implementing creative Marketing 5.0 strategies through digital technology, and strengthening financial stability through proper bookkeeping and financial discipline. Evaluation was conducted using pre-tests and post-tests, which indicated an improvement in participants’ theoretical understanding of the topics discussed. To ensure sustainable outcomes, follow-up mentoring is recommended to support the practical implementation of the knowledge and skills acquired during the program.